THE EFFECTIVENESS OF USING CIRC TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION ON RECOUNT TEXT - dion, Grydhion Yuschiyanxa; Tahrun; Marleni (SMART: Journal of Multidisciplinary Educational, 2024)
The title of this research is The Effectiveness Of Using Circ Technique To Improve Students' Reading Comprehension On Recount Text. The main problem of this study is that students have low motivation to read and also most students do not understand what they have read. Students' limited background knowledge in English. This study aims to determine the effect of Cooperative Integrated Reading and Composition (CIRC) learning model on students' learning outcomes. This research uses quantitative research the writer uses pre-test and post-test the population of this research is class X students of SMK Utama Bakti Palembang with class X TKJ II as the experimental class and X TKJ I as the control class. Data collection used is by using multiple choice test sheets. Based on the calculation results in the table, the Sig. (2-tailed) 0.000 < α (α = 0.025) and because tcount = 39.937 > ttable = 2.052 and with a significant value < 0.05 then H0 is rejected, which means that: "There is a significant effect of using Cooperative Integrated Reading and Composition technique to improve students' reading comprehension on recount text. Keywords: The Effectiveness  Of Using Circ Technique To Improve Students’ Reading Comprehension On Recount Text.